Hubungan Kecerdasan Sosial dengan Kepuasan Kerja Sama Kelompok dalam Small Group Discussion Pada Mahasiswa Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Udayana - Dewi, Ni Putu Santika; Wulanyani, Ni Made Swasti (Jurnal Psikologi Udayana, 2016)
One of the learning methods in Faculty of Medicine, Udayana University is Small Group Discussion (SGD), which comes in the form of discussions, with 10 until 13 students participating. Satisfaction of group members in cooperating with each other makes SGD run more effectively. Therefore, satisfaction becomes an important factor. SGD creates interactions among group members, while the quality of the interactions is influenced by social intelligence of the group members. This research aims at finding out the correlation between social intelligence and satisfaction of students in cooperating during SGD, as well as finding out how satisfied the students are in doing SGD. The subjects of this research are 274 students of Medical Science Program, Faculty of Medicine, Udayana University. The instruments of this research are Social Intelligence scale with reliability coefficient 0,871 and Satisfaction of Group Cooperating scale with reliability coefficient 0,938. The results from the analysis of product moment correlation indicates correlation number of 0,215 with significance level of 0,000 (p<0,05), which means there is a significant correlation between social intelligence and satisfaction of students in cooperating during SGD participated by the students of Medical Science Program, Faculty of Medicine, Udayana University. Higher social intelligence results in higher satisfaction level of students in cooperating, and vice versa.Keywords: social intelligence, satisfaction of group members in cooperating, Small Group Discussion